Opioid Prescribing Patterns by Obstetrics and Gynecology Residents in the United States. (2nd January 2018) - Baruch, Adam D.; Morgan, Daniel McBurney; Dalton, Vanessa K.; Swenson, Carolyn
ABSTRACT: Background: Despite the opioid epidemic in the U.S., little data exist to guide postoperative opioid prescribing in Obstetrics & Gynecology (Ob/Gyn). Objective: To describe Ob/Gyn resident opioid prescription patterns in the U.S. and assess influential factors. Methods: An anonymous survey was emailed to Ob/Gyn residents in the U.S. between January–February 2015. Respondents reported the typical number of discharge narcotic tablets prescribed following six common procedures. Responses to questions addressed potential factors influencing prescription practices and knowledge about opioid abuse in the U.S. Residents who prescribed a number of discharge narcotic tablets in the top quartile were compared to those who never did. Logistic regression was used to identify factors associated with top quartile prescribers. Results: 267 residents responded. Median number of discharge narcotics prescribed following cesarean section was 30 (IQR 28, 40) and after laparoscopic hysterectomy was 29 (IQR 20, 30). Factors associated with increased odds of prescribing in the top quartile included training in the West (aOR 3.15, 95% CI 1.05–9.45, p = 0.04) and agreeing with: "I prescribe postoperative narcotics to avoid getting reprimanded by attendings" (aOR 2.72, 95% CI 1.20–6.15, p = 0.02). Factors associated with decreased odds of prescribing in the top quartile included training in a community-based program (aOR 0.33, 95% CI 0.15–0.71, p = 0.005) and agreeing with: "I am conservative with the number of narcotics I prescribe after surgery" (aOR 0.34, 95% CI 0.17–0.71, p = 0.004). Conclusions/Importance: Opioid prescribing practices of Ob/Gyn residents are influenced by region of country, program-type, and factors related to hospital culture and personal insight.